Problems of Teaching and Learning Mathematics and Statistics in Daily Life of Higher Education Student at Rajamangala University of Technology Isan Kalasin Campus - นิติสุข, นิรันดร์; จงรัก, บรรจง; สหัสทัศน์, ชนกกานต์ (RMUTI Journal Humanities and Social Sciences, 2016)
The purpose of this research was to study the problems of mathematics and statistics used in everyday life of the five areas : education instructor, learning, teaching, assessment and learning support factors, that to compare the level of learning by variable education, gender and faculty as well as to know the needs of students and the teaching and learning solutions. Sample students enrolled a total of 142 people 1/2557 by stratified random sampling from a population of 302 people the tools used to collect the data. The scales on the top of the North Cape (Likert) and query multiple choice and open-ended. Data analysis by the percentage, the average score, the standard deviation, and compare using the t-test and f-test. Test methods of newman - kool’s (Newman - Keule) showed differences in the pair. The result found that overall, of each side is moderate by variable education and gender, and not different except the problem of evaluation that the difference was statistically significant 0.05. We found that the overall activity of teaching, the evaluation and the factors supporting teaching to have the difference were statistically significant at the 0.05. But level academic problems of students and the instructor were not different. Feedback from the students found that the needs and solve the problems of the teaching and learning of mathematics and statistics used in the daily lives of students, teachers should explain the lesson is clear, slowly teaching, teaching activities, increasing the number of exams, and papers to more entrepreneurs with a clear written explanation.